Study of relationship between soybean (Glycine max (L.) Merr.) planting spatial arrangements and velvetleaf (Abutilon theophrasti L.) population dynamic - Hamid SALEHIAN; Maryam NAJAFIAN (Acta Agriculturae Slovenica)
The velvetleaf is an important annual weed in the Mazandaran  province, Iran. Seeds are the only way of propagation and  renewal of this weed. More  knowledge was gained regarding  soil seed bank and its seed production to improve the  management of the velvetleaf weed in the future. There is a  minimal information concerning the impact of the soybean  planting pattern on the dynamics of the velvetleaf population.  For this reason two different fiel ds have been studied with the  cooperation of the Agriculture Discipline of the Islamic Azad  University, in Qaemshahr, Iran, during 2009 and 2012. In this  study the effect of two types of soybean row spacing were  used, 50 cm-wide and 36 cm - narrow, and three emergences  of the velvetleaf weed populatio n (periods 0-10, 10-20 and 20- 30 days after soybean sowing were implemented) were  studied. Seed production, leaf area and dry matter increased in  each plant population of the velvetleaf weed in the 50-cm  soybean rows. Mortality rates we re decreased in velvetleaf’s  seedling population in the wider spaced rows. By observation  it was seen an increased producti on of seeds in the first batch  of seedlings. It appears that we must remove the first weed  emergence flushes within three to four weeks after the  soybean emergence to prevent reduced yields in the soybean  crop and further increase of the velvetleaf seed bank.